Faktor-Faktor yang Mempengaruhi Kejadian Gizi Kurang pada Balita di Kelurahan Oesapa Kota Kupang - Delima Nala Ngoma; Apris A. Adu; Dominirsep O. Dodo (Media Kesehatan Masyarakat, 2019)
Malnutrition is a condition of a child's weight that is not appropriate to his age. Poor nutrition is still an unresolved health problem in Oesapa Village. The incidence of malnutrition continues to increase from 2016 to 2018. Malnutrition is influenced by several factors including: family income, maternal knowledge, maternal parenting and occupancy density. This study aims to analyze the influence of family income, maternal knowledge, parenting and occupancy density, on the incidence of malnutrition. This research is an analytic observational study, with a case control design. The sample size were 31 cases and 31 controls. The dependent variable in this study was the incidence of malnutrition and the independent variable consisted of family income, maternal knowledge, maternal parenting and occupancy density. Data analysis was performed univariately and bivariately. The results showed that, there are two variables that influence the incidence of malnutrition. The two variables are family income with p-value 0.01, OR 7.576, and mother's parenting with p-value 0.01, OR 3.870. To deal with these problems, the Social Service offier provider social assistance and oversee its use, so that it can be used in accordance with household needs. In addition, efforts to increase counseling on maternal parenting need to be done, which includes simple ways of providing and processing food, the process of bathing children under five and the application of hygiene practices, such as washing hands before processing and serving food.